2010 Reforms and Fifteenth General Review of Quotas : Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper ;, 2014)
In completing the Fourteenth General Review of Quotas (hereafter the 'Fourteenth Review') and approving the Proposed Amendment on the Reform of the Executive Board (hereafter the 'Board Reform Amendment'), the Board of Governors requested the Executive Board to bring forward the timetable for completion of the Fifteenth General Review of Quotas (hereafter the 'Fifteenth Review') to January 2014. The Executive Board was also requested to complete a comprehensive quota formula review by January 2013. These forward-looking elements were part of an agreed package of 2010 quota and governance reforms (hereafter the '2010 Reforms'). Each member committed to use its best efforts to complete the required steps for the effectiveness of the quota increases under the Fourteenth Review no later than the Annual Meetings in 2012.